Exposure to microbiological agents in indoor and occupational environments - Viegas, Carla Sofia Costa; Viegas, Susana; Gomes, Anita; Täubel, Martin; Sabino, Raquel (Springer, 2017)
This book intends to provide information about detection and health effects due to bacteria, fungi and viruses in indoor environments. The book will cover also information about preventive and protective measures to avoid health-hazardous. Case studies will be also addressed to enrich the book with the expertise of each invited author. The book also intends to fill a gap regarding information about all biologic agents, since most of the books available are dedicated to only one type of microorganisms. For various different biologic agents and metabolites this book will compile information about indoors presence, detection methods, exposure assessment and health effects. Several problems regarding the exposure of biologic agents will be presented through case studies, and also the implementation of preventive and protective measures to avoid/minimize exposure. Besides, all the book will focus on occupational health and/or public health point of view.
Keywords: Medical microbiology.; Microbial contamination.; elektronické knihy; electronic books